Caregivers' perspectives on good care for nursing home residents with Korsakoff syndrome. (May 2021) - Gerridzen, Ineke J; Hertogh, Cees MPM; Joling, Karlijn J; Veenhuizen, Ruth B; Verschuur, Els ML; Janssen, Tjeu; Depla, Marja F
Background: In the Netherlands, people with severe cognitive deficits due to Korsakoff syndrome are generally admitted to a specialized nursing home. Professional caregivers experience that these residents are often not aware of their deficits, and consequently, their willingness to accept care is relatively low. However, these residents need permanent support when performing daily tasks due to severe cognitive deficits. The combination of objective care needs and low subjective responsiveness makes caring for people with Korsakoff syndrome a complex undertaking. It is unknown how professional caregivers deal with this complex task and how they manage the associated ethical challenges. Objectives: The aim of this study was to explore the professional caregivers' perspectives on good care for residents with Korsakoff syndrome. Methods: A qualitative study design was used. Data were collected via semi-structured interviews. The Framework Method was used for the thematic analyses of the interview data. Participants and research context: Five specialized nursing homes participated in this study. Twelve professional caregivers, including nurses, nursing assistants, and support workers, were selected based on the ability to provide rich information on the study topics and to capture a variety of demographic and professional characteristics. Ethical considerations: The institutional review board of the VU University Medical Center Amsterdam approved the research protocol. The study was conducted in accordance with the ethical principles for medical research involving human subjects. Findings: Three perspectives on good care emerged: (1) making daily life a joint effort, (2) being steadfast, and (3) treating with respect. Discussion and conclusion: Professional caregivers try to achieve responsiveness in people with Korsakoff syndrome in three different ways. These perspectives reflect fundamentally different views on the care relationship and the autonomy of the resident. By elucidating the three perspectives, we hope to promote the practitioners' reflection on their own ideas about good care for people with Korsakoff syndrome.